Student successes with Thinking Maps school-based research, results, and models for achievement using visual tools - Hyerle, David N.; Alper, Larry (Thousand Oaks, Calif. Corwin Press, 2011)
This new edition presents eight powerful visual models that boost all learners' metacognitive and critical thinking skills. Updates include new research, examples, and applications.
Thinking Maps as a transformational language for learning / David Hyerle -- Why and how Thinking Maps work : a language of brain and mind / Kimberly M. Williams -- Leveling the playing field for all students / Bonnie Singer -- Tools for integrating theories and differentiating practice / Alan Cooper -- Closing the "gap" by connecting culture, language, and cognition / Yvette Jackson -- Maps for the road to reading comprehension : bridging text structures to writing prompts / Thomasina DePinto Piercy and David Hyerle -- Empowering students from thinking to writing / Jane Buckner -- The challenge of high-stakes testing in middle school mathematics / Janie B. MacIntyre -- Thinking like a scientist / Lou-Anne Conroy and David Hyerle -- Thinking technology / Daniel Cherry -- A first language for thinking in a multilingual school / Stefanie R. Holzman -- Feeder patterns and feeding the flame at Blalack Middle School / Edward V. Chevallier -- Becoming a thinking school / Gill Hubble -- Stories from Mississippi : results from college to kindergarten / Marjann Kalehoff Ball -- The Singapore experience : student-centered fluency / Ho Po Chun -- Inviting explicit thinking / Sarah Curtis -- Coaching and supervising reflective practice / Kathy Ernst -- Thinking Maps : a language for leading and learning / Larry Alper -- Bifocal assessment in the cognitive age : Thinking Maps for assessing content learning and cognitive processes / David Hyerle and Kimberly M. Williams.
Keywords: Visual learning -- United States; Learning, Psychology of; Thought and thinking